High Speed Video System for Tissue Measurement Based on PWM Regulated Dimming and Virtual Instrumentation - Koniar, D.; Hargaš, L.; Štofan, S.; Hrianka, M. (Elektronika ir Elektrotechnika, 2010)
Paper focuses on main topics in high speed video acquisition system designing. This video system is used in sophisticated diagnostics of microstructures in human tissue, especially respiratory epithelium cilium. System is linked with optical microscope and uses a phantom generator controlled with DSP processor for calibration and debugging. Algorithms and software are developed as user friendly virtual instruments.